Overview of State of Charge (SOC) Estimation Methods of EV Batteries FAST CHARGING SYSTEM OF ELECTRIC VEHICLE BATTERIES - Karimkhadjayev Nazirjon; Ismatov Biloldin (Лучшие интеллектуальные исследования, 2024)
Abstract: The State of Charge (SOC) is a pivotal parameter in the management of electric vehicle (EV) batteries, influencing their efficiency, lifespan, and overall performance. Accurate SOC estimation is crucial for maximizing battery utilization and ensuring reliable operation of EVs. This review consolidates current research advancements in SOC assessment methods, emphasizing improvements and practical applications.